Direct Testing for KPC-Mediated Carbapenem Resistance from Blood Samples Using a T2 Magnetic Resonance Based Assay - Giulia De Angelis; Riccardo Paggi; Thomas J. Lowery; Jessica L. Snyder; Giulia Menchinelli; Maurizio Sanguinetti; Brunella Posteraro; Antonella Mencacci (MDPI AG, 2021)
Molecular-based carbapenem resistance testing in Gram-negative bacterial bloodstream infections (BSIs) is currently limited because of the reliance on positive blood culture (BC) samples. The T2Resistance™ panel may now allow the detection of carbapenemase- and other β-lactamase encoding genes directly from blood samples. We detected carbapenem resistance genes in 11 (84.6%) of 13 samples from patients with BC-documented BSIs (10 caused by KPC-producing Klebsiellapneumoniae and 1 caused by VIM/CMY-producing Citrobacter freundii). Two samples that tested negative for carbapenem resistance genes were from patients with BC-documented BSIs caused by KPC-producing K. pneumoniae who were receiving effective antibiotic therapy. In conclusion, our findings suggest that the T2Resistance™ panel can be a reliable tool for diagnosing carbapenem-resistant Gram-negative bacterial BSIs.